DEVELOPMENT OF PARADIGMATIC INTEGRATIC PATTERN AT FATONI THAILAND UNIVERSITY - Sudarman Sudarman (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2018)
Abstract; This article is titled Development of Paradigmatic Integratic Patteren at Fathoni Thailand University. In this connection, the application of the pattern of Islamization or scientific integration is motivated by differences in understanding of the concept of scientific integration and local socio-cultural settings that are the background of the college. Fathoni University carries a scientific paradigm in the form of an attempt to subdue modern science (aqli) to the will of revelation, so that science not only has a worldly purpose, but also has a universal purpose. This kind of paradigm of Islamization of science is similar to the path taken by the ulema of Ahlu al-Sunnah in the classical Islamic period. They always put forward the revelation in the development of religious knowledge related to monotheism and fiqh. this road they take to remember the limitations of human reason in finding the basis and purpose of a science .